2007
DOI: 10.1590/s0100-69912007000400005
|View full text |Cite
|
Sign up to set email alerts
|

Simpactectomia lombar retroperitoneoscópica para tratamento da hiper-hidrose plantar

Abstract: RESUMO: Objetivo: Observar o seguimento de até quatro anos de mulheres submetidas à simpatectomia lombar por retroperitonioscopia, procurando identificar seus efeitos colaterais, bem como sua efetividade no controle da hiper-hidrose plantar. Métodos: Entre junho/2002 e julho2006, operamos 44 pacientes com hiperidrose plantar. Todas apresentavam hiper-hidrose plantar persistente pós simpatectomia torácica com exceção de uma única paciente com diagnóstico de hiperidrose plantar primária. Resultados: O seguimento… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
3
0
2

Year Published

2008
2008
2023
2023

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 12 publications
1
3
0
2
Order By: Relevance
“…When patients were asked for their impression about CS at six months after the operation, the results were similar to those of our previous study 28. Of the 15 patients, 53% reported worsening of CS, mainly on hotter days or when performing physical activities.…”
Section: Discussionsupporting
confidence: 77%
“…When patients were asked for their impression about CS at six months after the operation, the results were similar to those of our previous study 28. Of the 15 patients, 53% reported worsening of CS, mainly on hotter days or when performing physical activities.…”
Section: Discussionsupporting
confidence: 77%
“…(19,20) It has been observed that these alterations occur at several levels and that, different from thoracic sympathectomy, they are independent from the sympathetic chain resection level, since the surgeon always attempts to remove the L2 and L3 lumbar ganglia. (36) Few studies have associated lumbar sympathectomy, hyperhidrosis and compensatory sweating. In one study, the appearance of CH was reported in five of eight cases of endoscopic lumbar sympathectomy to control plantar hyperhidrosis.…”
Section: Sympathetic Chain Reinnervationmentioning
confidence: 99%
“…7 Studies have also reported that lumbar sympathectomy may increase CS in more than half of cases. 9,30,31,35 In our study, at a minimum of 12 months after RLS, there were no new cases reported of CS. Three of the 49 patients had an improvement in CS on the abdomen and areas between the thighs.…”
Section: Discussionmentioning
confidence: 40%